Effects of sugarcane production in southwestern Kenya on income and nutrition - Kennedy, Eileen T. (International Food Policy Research Institute, 1994)
In 1984, at the request of the Government of Kenya, IFPRI initiated a study to evaluate the income and nutritional effects of a shift from maize to sugarcane production. The government was concerned that in areas undergoing this transition to commercial agriculture, particularly to sugarcane production, a deterioration in household-level food security and preschooler nutritional status was occurring.